Developing Students’ Dialogue Journal Writing (DJW) of Recount Text at the Tenth Grade of SMK Negeri 1 Lahewa in 2022/2023 - Nazara, Windi Lara Sari; Harefa, Afore Tahir; Telaumbanua, Yasminar Amaerita; Telaumbanua, Kristof Martin Efori (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2023)
This research was motivated by a preliminary study at SMK Negeri one Lahewa and the results obtained that students were still lacking in writing recount texts. In addition, the use of learning media by teachers in teaching is still conventional, especially in recount text material. The purpose of the study was to determine the feasibility, practicality, effectiveness, of dialogue journal writing of recount text. This research is research and development. The results of the study, the developed Dialogue Journal Writing DJW of Recount Text has been tested for validity by linguists with an average percentage of eighty three percent and by media experts ninety-one point twenty-five percent with very valid criteria, to be practical to be used by students with an average percentage score of ninety point twenty nine in individual trials, eighty-four point seventy-two percent in small group trials, for field practicality trials of eighty-five point sixty-nine percent to effective to use with an average percentage value of eighty six with very effective criteria.